Nutritional status of toddlers attending day care centres in Newton Park, Nelson Mandela Bay - Rauch, Carli (University of the Free State, 2016)
Current research highlights the importance of optimal nutritional status during the first three years of life, specifically toddlerhood (1 – 3 years), since this phase is characterised by crucial physical and neurological development, the establishment of lasting food preferences and eating habits, as well as an increased risk for stunting, rapid early weight gain and predisposition to development of Non-communicable Disease (NCD) in later life. However, despite the importance of optimal nutritional status in this age group, recent statistics reflect a global trend of children under five years consuming energy-dense diets with inadequate dietary diversity, hence characteristic of the nutrition transition. As a result, the incidence of stunting remains high, with statistics reflecting an increasing rate of overweight and obesity in this age group, which is suggestive of the double burden of malnutrition (DBM). The Eastern Cape Province ranked among the provinces with the highest rate of food insecurity, poor quality dietary intake and stunting in young children, yet no studies on the nutritional status of toddlers in this province could be located. Therefore, the current study aimed to evaluate the nutritional status, including socio-demographic information, clinical signs, anthropometry, dietary intake and child food security, of toddlers attending day care centres in Newton Park, Nelson Mandela Bay. A quantitative descriptive study was conducted over the period of 20 April to 27 May, recruiting 55 consenting toddlers with their primary caregiver, who attended one of the six consenting day care centres in Newton Park, Nelson Mandela Bay. Socio-demographic, child food security and dietary intake information were recorded via questionnaires by means of one-on-one semi-structured interviews conducted with caregivers, while anthropometric data was collected using standard measuring techniques and interpreted according to the current child growth standards by the World Health Organization’s (WHO). Participants were predominantly English speaking (56.4%) Caucasian (56.4%) and resided in non-overpopulated formal dwellings (100%) with an average of three to four household members (72.7%). The average monthly household income reported by most caregivers (80%) were above the tax return threshold; R10 000 to R40 000 (low to average monthly income).However, considering a mean household size of three to four members, this level of income may have posed a risk for the development of low food security. Anthropometric analysis reflected the DBM, in that participants were affected by both stunting (7.3%) and overweight / obesity (9.1%). Stunting affected mostly the older age subgroup, while overnutrition was identified in those as young as one year of age. These results highlighted the presence of the DBM, as well as the associated increased risk for NCDs in adulthood. A statistically significant association was found between the level of food security and growth (weight-for-age and length/height-for-age measurements) of participants. Therefore, since one in five participants had a low level of food security, food insecurity also contributed to poor growth and development. Most participants consumed energy-dense diets, consisting largely of refined carbohydrates (CHO), high fat and low fibre sources, as confirmed by the excessive consumption of animal protein sources, added fat, sugars and processed food, in detriment of fruit, vegetables, legumes, whole grain starches and dairy. Additionally, only three participants (5.5%) consumed diets with optimal dietary diversity, suggesting a trend of energy-dense foods, high in added sugar and / or fat, like cookies and sugar-sweetened beverages (SSB), taking preference over nutrient-dense sources, such as fruit, vegetables and wholegrain starches. In summary, results from the current study supported reflected trends of nutrition transition, leading to the DBM and thus an increased risk of NCD and NCD’s in adulthood. Results highlight the need for nutrition intervention in the form of educational sessions aimed at parents and day care centre personnel, aiming to ensure optimal development and better future health in toddlers from Nelson Mandela Bay.

Huidige navorsing beklemtoon die uiterste belang van optimale voedingstatus tydens die eerste drie jaar van ‘n kind se lewe, met die fokus op kleuters (1 tot 3 jaar), siende dat kinders kritieke fisiese en neurologiese ontwikkeling ondergaan tydens die fase, sowel as die ontwikkeling van blywende kosvoorkeure en eetgewoontes. Dus is dit vanselfsprekend dat kleuters ook meer vatbaar is vir ondervoeding, wat lei tot oormatige vroeë massatoename en ‘n verhoogde risiko vir die ontwikkeling van chroniese siektes as volwassenes. Ten spyte van die feit dat voedingstatus in kleuters ‘n internasionale prioritiet moet wees, reflekteer huidige statistieke ‘n internasionale patroon van energiedigte dieët-inname met lae dieëtdiversiteit in kinders onder die ouderdom van vyf jaar, wat kenmerkend is van ‘n Westerse dieëtpatroon, ook bekend as die “nutrition transition”. Vervolgens is daar steeds ‘n hoë persentasie kinders met groei-inkorting, terwyl toenemend meer oorgewig en vetsugtige jong kinders voorkom in hierdie ouderdomsgroep, wat beduidend is van die dubbele las van wanvoeding. Die Oos-Kaap Provinsie is tans een van die provinsies met die hoogste voorkoms van lae voedselsekuriteit, lae-kwaliteit dieëtinname en groei-inkorting in jong kinders, alhoewel geen studies wat die voedingstatus van kleuters in hierdie area ondersoek, gevind kon word nie. Die doelwit van die huidige studie, was om die voedingstatus, insluitende die sosio-ekonomiese inligting, kliniese tekens, antropometrie, dieëtinname en die kinder voedselsekuriteit, van kleuters wat ingeskryf is by dagsorgsentrums in Newton Park, Nelson Mandelabaai, te evalueer. ‘n Beskrywende, kwantitatiewe studie was uitgevoer oor die periode van 20 April tot 27 Mei, 2015, waartydens 55 kleuters van gewillige dagsorgsentrums in Newton Park genader is, en ingesluit is, met die toestemming van hulle primêre toesighouers Inligting rondom sosiodemografie, kinder voedselsekuriteit en dieëtinname is ingesamel deur middel van vraelyste wat voltooi is tydens individuele, semi-gestruktureerde onderhoude tussen die navorser en deelnemende toesighouers. Standaard meettegnieke is toegepas om antropometriese data in te samel, en die resultate is geïnterpreteer volgens die nuutste groeistandaarde van die World Health Organization (WHO). Die meerderheid van die deelnemers was Blank (56.4%) en Engelssprekend (54.5%), van wie almal aangedui het dat hulle formele baksteen wonings besit. Daar was gemiddeld drie tot vier mense per huidhouding (72.7%), dus nie oorbevolk nie. Die maandelikste huishoudelike inkomste van die meerderheid studiedeelnemers was bo die belastingsafsnypunt (80%); R10 000 to R40 000 (onder gemiddeld na ‘n gemiddelde inkomste). Dus kon ‘n lae na gemiddelde inkomstevlak moontlik ‘n bydraende faktor tot lae voedselsekuriteit gewees het, siende dat die gemiddelde huishouding uit drie tot vier lede bestaan het. Antropometriese analise was beduidend van die dubbele las van wanvoeding, siende dat daar beide groei-inkorting (7.3%), sowel as oormassa / vetsug (9.1%) onder studiedeelnemers geïdentifiseer is. Groei-inkorting het meestal die ouer groep studiedeelnemers affekteer, terwyl oormassa / vetsug selfs in die eenjariges waargeneem is. Dus is hierdie studiedeelnemers geneig tot ‘n hoër risiko vir chroniese leefstylsiektes as volwassenes. Daar is ‘n statisties betekenisvolle assosiasie tussen die vlak van voedselsekuriteit en die groei en ontwikkeling van studiedeelnemers (massa-vir-ouderdom en lengte-vir-ouderom mates). Gevolglik is die waargenome een uit vyf studiedeelnemers met lae voedselsekuriteit, ‘n bydraende faktor tot onvoldoende groei / ontwikkeling. Meeste van die huidige studiedeelnemers se dieët het bestaan uit energiedigte bronne - oormatig verfynde koölhidrate, hoë vet en lae veselbronne. Hierdie inname is bevestig deur die hoë inname van dierproteïne en geprosesseerde kosse (hoog in bygevoegte suiker en vette). Gevolglik het studiedeelnemers ‘n lae inname van voedingstofryke voedselbronne, soos groente, vrugte, peulgroente en suiwel getoon. Slegs drie studiedeelnemers (5.5%) het ‘n dieëtinname met optimale dieëtdiversiteit getoon, wat beduidend was van ‘n neiging om voedingstofryke kos, soos vrugte, groente en volgraan stysels, te vervang met energieryke bronne, vol ekstra suiker en / of vet, soos koekies en versoete drankies. Ter opsomming het die resultate van die huidige studie getoon dat alle lede van die bevolking, insluitende jong kinders, toenemend ‘n Westerse dieëtpatroon aanneem (“nutrition transition”), wat lei tot ‘n hoër voorkoms van die dubbele las van wanvoeding en dus toekomstige chroniese leefstylsiektes in hierdie ouderdomsgroep. Daar is dus ‘n behoefte aan voedingsintervensie, in die vorm van inligting en opleidingsessies vir ouers en personeel van dagsorgsentrums, met die oog op optimale ontwikkeling en beter toekomstige gesondheid van kleuters in Nelson Mandela Baai.
Dissertation (M.Sc. Dietetics (Nutrition and Dietetics))--University of the Free State, 2016
Keywords: Toddler; Nutritional status; Double burden of malnutrition; Nutrition transition; Non-communicable disease; Dietary diversity; Food insecurity; Body mass index-for-age measurements; Mid-upper arm circumference measurements; Carbohydrates; Malnutrition in children--South Africa--Nelson Mandela Bay; Children--Nutrition--South Africa--Nelson Mandela Bay